Preferensi Konsumen Pengguna E-Commerce yang Memengaruhi Kesadaran akan Perlindungan Konsumen pada Generasi X - Widyastuti, Hardiana; Prastitya, Tita Ajeng (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Nowadays people choose to buy product using the internet. E-Commerce is an alternative channel to buy goods or services, but the fact that the goods or services received by consumers are not always satisfying. In dissatisfication case, consumers have rights to sued. In this case, some consumers prefer to accept the deficiencies, because consumer’s lackness of consumer protection awareness. Consumer protection is an effort that guarantee consumer’s safety with legal aspect. The purpose of this study is to analyze the factors that influence the awareness of consumer protection. The method to determine the respondent is done by using purposive sampling with sample of 200 respondents, X Generation that had already used e-commerce. The result are then analyzed by descriptive analysis and Structural Equation Modeling with Partial Least Square. Result of this research shows that consumer protection awareness affected by access to information and experience. The information and experience that consumer have will be a lesson for the next online transaction.